Estimation of the adherence of mortars using ultrasound - Khaldi, Nacera; Belachia, Mouloud; Benouis, Abdelhalim (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Mortars are subjected to severe external stresses such as freezing, thawing, and drying during their lifetime. These stresses can lead to a loss of adhesion between the support and the mortar. The strength of the substrates with respect to their ability to receive a coating (mortar) is characterized in particular by the value of minimum tear resistance of the surface to be coated. In this work, the use of a non-destructive method which is both fast and easy to implement is employed to evaluate this support-mortar adhesion.
Keywords: adherence of mortars; mortar; support; adhesion; thickness; ultrasound method; pull out; przyczepność zaprawy; zaprawa; ocena przyczepności; metoda ultradźwiękowa; ultradźwięki